Investigating the influencing factors in Selecting a Field Specialty for Medical Students of Ahvaz Jundishapur University of Medical Sciences - Abdolhussein Shakurnia; Seyed Saeid Seyedian (Mashhad University of Medical Sciences, 2022)
Background: The choice of a medical specialty is an important issue that has implications both for medical students and the healthcare system. This study aimed to explore the Specialty preferences and motivational factors influencing career preferences of medical students in Ahvaz, Southwest Iran. Methods: A questionnaire-based, cross sectional study was performed on 198 medical students during the academic year 2018-2019. Data were collected using a questionnaire scored based on a five-point Likert scale. Data were analyzed with SPSS version 19 using descriptive and analytical statistics. P <0.05 was considered significant. Results: The mean age of the students was 26.8±1.4 years; 71(36%) were male and 134(68.4%) were single. The most popular specialty was radiology (n=45; 22.7%), followed by dermatology (n=35; 17.7%) and ophthalmology (n=31; 15.7%). The least popular specialties were psychiatry (n=1; 0.5%), emergency medicine (n=1; 0.5%), and anesthesia (n=0; 0.0%). Most of the reasons for specialty choice were personal interest (4.54 out of 5), achieving abilities and competence to promote health in the community (4.05), and income and prestige (4.04). Discussion: This study provides insights into the motivational factors that influence the Specialty preferences of Iranian medical students. The most influencing factors in specialty choice were personal interest, achieving abilities and competence to promote community health, and income and prestige, respectively. Identification of factors influencing specialty choice among medical students can help to plan postgraduate training and health manpower programs.